Studi Komparatif Hukum Perceraian di Indonesia dan Iran - Aditya Setiawan (Kartika: Jurnal Studi Keislaman, 2026)
This study focuses on a comparative analysis of divorce regulations in Indonesia and Iran. The comparison is conducted to identify similarities and differences, so that the findings of the study can be used as material for reflection in addressing shortcomings, inspiring the formulation of regulations, and helping to unravel the problem of dualism in divorce regulations in each country. The method used is normative legal research with a comparative approach, using secondary data collected through documentary studies. The main sources of research include Law No. 1 of 1974 concerning Marriage, Presidential Instruction No. 1 of 1991 concerning the Compilation of Islamic Law, and marriage laws in Iran, namely قانون حمايت خانواده Qanun Hemayat-e Khanevadeh (Family Protection Law). Data analysis was carried out in several stages, namely editing, classifying, verifying, analysing, and concluding, so as to obtain a systematic and accountable picture. The results of the study show that divorce in Indonesia and Iran can both be carried out through the talak mechanism. However, at the technical level, there are differences, particularly regarding the recording of divorce: in Indonesia, divorce is proven by a court decision, while in Iran it can be based on a statement of incompatibility or a divorce decree from the court